2019
DOI: 10.1021/acs.jced.9b00356
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Liquid Density of Ammonia/Athabasca Bitumen Mixtures at Temperatures up to 463 K: Measurements and Modeling

Abstract: We report the experimental data of ammonia solubility in Athabasca bitumen measured at different temperatures and pressures ranging from 348 to 463 K and 1 to 4 MPa, respectively. The liquid-phase density of ammonia-saturated bitumen was measured for the samples that were taken during solubility measurements. The experimental data for ammonia solubility in bitumen were modeled using the Peng–Robinson equation of state. The volume-shift parameters of ammonia were tuned to represent the experimental density data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The solvents (chemicals) used to extract bitumen from oil sands are C3, NH 3 , dimethyl ether (DME), butane (C4), hexane (C6), ethyl acetate (EA), and field natural gas condensates. The thermophysical properties of the solvents/bitumen mixtures used in numerical simulations of the SA recovery processes have been obtained from the literature. , A base case SAGD is also simulated for comparison. The injection time of solvents (chemicals) is selected to allow the production of more than 75% of the original oil in place.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The solvents (chemicals) used to extract bitumen from oil sands are C3, NH 3 , dimethyl ether (DME), butane (C4), hexane (C6), ethyl acetate (EA), and field natural gas condensates. The thermophysical properties of the solvents/bitumen mixtures used in numerical simulations of the SA recovery processes have been obtained from the literature. , A base case SAGD is also simulated for comparison. The injection time of solvents (chemicals) is selected to allow the production of more than 75% of the original oil in place.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The solvents (chemicals) included in the fluid model are propane, butane, hexane, field condensates, dimethyl ether, ammonia, and ethyl acetate. All thermophysical properties of the solvents (chemicals) used in numerical simulations have been previously reported. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Sadeghi Yamchi et al performed the liquid–liquid study of the DME/bitumen system and reported the density, viscosity, and DME composition of the light phase of the mixture. Bin Dahbag et al also reported measurements of ammonia solubility in Athabasca bitumen and ammonia-saturated oil density at different temperatures and pressures, with application to solvent-aided bitumen recovery from oil sands.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, flooding the reservoir with alkaline solutions change the rock wettability toward more water-wet due to the presence of polar compounds in alkaline solutions, which are adsorbed to the rock surface containing different charges . In addition to the generation of in situ surfactants, ammonia effectively reduces the viscosity and the total acid number (TAN) of acidic crude oil making it more valuable and desired for refining. ,, According to ASTM D664, the total acid number is the milligram of potassium hydroxide (KOH) that should be added into the solution to neutralize the acidic compounds found in 1 gram of the crude oil . Carbon dioxide is another important product resulting from the decomposition of the urea solution at the SAGD steam chamber conditions.…”
Section: Introductionmentioning
confidence: 99%